2006
DOI: 10.1577/m04-207.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Crappie Recruitment in Ohio Reservoirs with Spawning Stock Size, Larval Density, and Chlorophyll Concentrations

Abstract: Abstract.-Stock-recruit models typically use only spawning stock size as a predictor of recruitment to a fishery. In this paper, however, we used spawning stock size as well as larval density and key environmental variables to predict recruitment of white crappies Pomoxis annularis and black crappies P. nigromaculatus, a genus notorious for variable recruitment. We sampled adults and recruits from 11 Ohio reservoirs and larvae from 9 reservoirs during 1998-2001. We sampled chlorophyll as an index of reservoir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Further, declines in growth caused by increased intraspecific competition may lead to decreased reproductive investment and reductions in recruitment (Bunnell et al. ; Michaletz ). Concentrating harvest on large individuals has been shown to cause recruitment overfishing in salmonids by removing the individuals that contribute the greatest reproductive output (Sánchez‐Hernández et al.…”
Section: Discussionmentioning
confidence: 99%
“…Further, declines in growth caused by increased intraspecific competition may lead to decreased reproductive investment and reductions in recruitment (Bunnell et al. ; Michaletz ). Concentrating harvest on large individuals has been shown to cause recruitment overfishing in salmonids by removing the individuals that contribute the greatest reproductive output (Sánchez‐Hernández et al.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we use the Emery and Brown (1978) regression [Fecundity = −580.6 + 58.88(weight); note Emery and Brown (1978) failed to include the negative sign in front of the intercept] for the 1963-1984 year-classes, and our regression for 1985-2004 year-classes. To fit the Ricker (R =Se [a-bS] e ɛ ) and BevertonHolt (R ={aS /[b + S]}e ɛ ) models, where R equals age-3 bloater recruits (in millions of individuals), S equals population egg production (in billions of eggs), and e ɛ equals the lognormal error term, we followed Bunnell et al (2006b) where both sides of the equation were log etransformed [Ricker: log e (R) = log e (S)+ a − bS + ɛ, Beverton and Holt: log e (R) = log e (aS) − log e (b + S)+ɛ)] and non-linear regression (Proc NLIN, SAS Institute, 1999) was used to estimate the parameters. For each model, r 2 was calculated as the model sum of squares divided by the corrected total sum of squares.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, angling exploitation likely caused recruitment overfishing of a Kansas walleye population (Quist et al 2010). A recreational black crappie, Pomoxis nigromaculatus (LeSueur), fishery exerted a 42% exploitation rate, which was near the recruitment overfishing threshold (Dotson et al 2009). Bunnell et al (2006 suggested that harvest restrictions would improve recruitment of white crappie P. annularis for some Ohio reservoirs, which indicated that some stocks were recruitment overfished.…”
Section: Introductionmentioning
confidence: 99%